PELATIHAN PEMBUATAN ROKET AIR UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DI DESA SIRNAJATI - Julviansyah, Devin; Ardi, Ardi; Maysaroh Chairunnisa, Nurlaila (An-Nizam, 2024)
The community service activity programme aims to increase the motivation of junior high school students in Sirnajati Village, Cibarusah Subdistrict, Bekasi Regency in learning science or natural science through the use of a training programme interspersed with games to make water rockets. Water rockets are an implementation of physics, fluids, and mechanics that are interesting to discuss. Basically, water rockets have complex physics variables in the motion of the rocket, but can be described and applied simply to inspire students in learning physics and its applications. The method used is stimulation or practical demonstration of the process or operation of an object in relation to educational material, in this case water rockets. The results of this community service programme showed that more than 90% of most students gave a positive response to learning and were able to increase motivation and educational activities during the learning process.